Determination of Λ-Cyhalothrin in palm and palm kernel oils using tandem solid-phase extraction cartridges - Muhamad, H.; Zainudin, B.H.; Abu Bakar, N.K. (2012)
This article outlines a new method based on low-temperature fat precipitation extraction with acetonitrile and graphitised carbon black/primary secondary amine (GCB/PSA) solid-phase extraction clean-up for the extraction of lambda-cyhalothrin residue in both crude palm oil (CPO) and crude palm kernel oil (CPKO). Determination of lambda-cyhalothrin was then carried out using gas chromatography (GC) equipped with an electron capture detector (ECD). Analyses for lambda-cyhalothrin in palm oil and palm kernel oil samples spiked with different levels of lambda-cyhalothrin (0.05, 0.08, 0.1, 0.5, and 1.0 mu g g(-1)) were performed. Mean recoveries for six replicates ranged from 82 to 98 for CPO and from 86 to 94 for CPKO, with relative standard deviation (RSD) values of less than 10 in most cases. The limit of detection for lambda-cyhalothrin in both CPO and CPKO was 0.05 mu g g(-1). The method was successfully applied to the analysis of lambda-cyhalothrin in CPO samples obtained from local palm oil mills throughout Malaysia. No lambda-cyhalothrin was found in the 30 samples analysed.